INTER-PHASE CONTACTS IN BITUMEN-MINERAL SYSTEMS AND THEIR STRENGTHENING - Ya. N. Kovalev (Наука и техника)
Presently bitumen-mineral materials (including asphalt-concrete) comprise nearly 98 % for construction of expensive road pavement. Large resources of local minerals (quartz sand) and industrial wastes in the form of used molding sand (foundry by-product) are widely applied for reduction of their cost. Such approach is economically and ecologically reasonable but it requires its justification because an adhesion interaction in the bitumen-quartz substrate system (with SiO2 more than 95 %) is rather poor in natural state and due to water action it is still more decreasing. In this connection an objective necessity arises to modify significantly technology of bitumen-mineral compositions for ensuring reliability of road pavements while using silicon components.All the ideas pertaining to strengthening of adhesion bonds in the “quartz mineral substrate - bitumen” system are traditionally of physical and chemical nature and they presuppose mainly usage of colloidal chemistry methods. The paper considers the matter on the basis of molecular kinetic theory of matter taking into account the fact that there is absence of generally accepted calculations for intermolecular interactions of components in the SiO2 - organic matrix material system.As a theoretical supposition the following well-known regulatory principle in physics is used: as every atom or molecular have its own electromagnetic field then action of external electromagnetic fields initiates their interaction that leads to excitement of electrons, deformations and rupture of chemical bonds. Literature analysis shows that the existing electric bonds between components of the SiO2 - organic matrix material system provide the possibility to apply various electro-physical methods having an effect on these components with the purpose to strengthen their adhesion interaction.The paper investigates matters for determination of bond energy during physical adsorption and adhesion in the SiO2 - organic matrix material system with due account of the indicated principles.